Diagnostic and epidemiological landscape of anaerobic bacteria in Europe, 2020-2023 (ANAEuROBE) - Boattini, Matteo; Bianco, Gabriele; Bastos, Paulo; Mavromanolaki, Viktoria Eirini; Maraki, Sofia; Spiliopoulou, Anastasia; Kakouris, Vasileios; Kalchev, Yordan; Budimir, Ana; Bedenić, Branka; Rubic, Zana; Licker, Monica; et al. (International journal of antimicrobial agents, 2025)
INTRODUCTION: Despite being implicated in a wide spectrum of community- and healthcare-acquired infections, anaerobes have not yet been incorporated into systematic surveillance programs in Europe. METHODS: We conducted a multicentre retrospective observational study analysing all anaerobic strains isolated from blood cultures in 44 European Hospital Centres over a 4-y period (2020-2023). Diagnostic approach, epidemiology, and antimicrobial susceptibility according to EUCAST v. 15.0 were investigated. RESULTS: Our study included 14,527 anaerobes, most of which were Gram-positive (45%) or Gram-negative (40%) bacilli. MALDI-TOF coupled to mass spectrometry was the most widely used tool for species identification (98%). Antimicrobial susceptibility testing was performed in the vast majority of centres, using mostly gradient diffusion strip (77%) and disk diffusion (45%) methods according to EUCAST guidelines. The most prevalent species were Cutibacterium acnes (18.7%), Bacteroides fragilis (16.3%), Clostridium perfringens (5.3%), Bacteroides thetaiotaomicron (4.2%), Fusobacterium nucleatum (3.5%), and Parvimonas micra (3.4%). C. acnes showed high resistance to benzylpenicillin (18%), clindamycin (39%), and imipenem (19% and 13% by MIC methods and disk diffusion, respectively). B. fragilis showed high resistance to amoxicillin/clavulanate (24%), piperacillin/tazobactam (22% and 14% by MIC methods and disk diffusion, respectively), clindamycin (22% by both MIC methods and disk diffusion), meropenem (13%), and metronidazole (10%, only by disk diffusion). A similar resistance pattern was observed in B. thetaiotaomicron, Bacteroides ovatus, and Parabacteroides distasonis. C. perfringens showed high resistance to clindamycin (69% and 45% by MIC methods and disk diffusion, respectively), while benzylpenicillin and metronidazole maintained over 90% activity. F. nucleatum showed high resistance to benzylpenicillin (11%), while Fusobacterium necrophorum showed alarming rates of resistance to clindamycin (12%), meropenem (16%) and metronidazole (11%). CONCLUSIONS: This study presented an up-to-date analysis of the diagnostics and epidemiology of anaerobic bacteria in Europe, providing insights for future comparative analyses and the development of antimicrobial diagnostic and management strategies, as well as the optimization of current antibiotic treatments.
Keywords: Bacterial Infections; retrospektivní studie; antibakteriální látky; Europe; Microbial Sensitivity Tests; Clostridium; Bacteroides; Antimicrobial resistance; Sepsis; Evropa; bakteriální infekce; Anaerobes; anaerobní bakterie; lidé; Anti-Bacterial Agents; Bacteria, Anaerobic; Humans; mikrobiální testy citlivosti; Blood culture; Retrospective Studies